The Utilization of Teaching Modules Through Learning Outside the Classroom in Improving Understanding of History Learning in Class X of SMA Negeri 5 Palu - Rezki, Hikmah Setia; Nuraedah, Nuraedah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the use of teaching modules through learning outside the classroom in improving students' understanding of history learning at SMA Negeri 5 Palu. The background of this research is based on the low interest and understanding of students in historical material which is often considered boring and only focuses on theory. For this reason, more contextual learning innovations are needed by utilizing teaching modules that are arranged according to the needs of students and implemented through learning outside the classroom. The research method used is the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research subjects were students of class X MIA 4 and a follow-up trial was carried out in class XI Social Studies to see the consistency of the results of the implementation of the teaching module. The research instruments include observation sheets, comprehension tests, and student response questionnaires. The results of the study show that the use of teaching modules in learning outside the classroom is able to increase activeness, foster curiosity, and provide a more meaningful learning experience. The data from the evaluation showed an increase in students' understanding of history material both in class X and in the trial in class XI with the very good category. Thus, the use of teaching modules through learning outside the classroom can be used as an alternative strategy to improve the quality of students' understanding of learning history at SMA Negeri 5 Palu.